2014
DOI: 10.1111/all.12374
|View full text |Cite
|
Sign up to set email alerts
|

Decreased diversity of nasal microbiota and their secreted extracellular vesicles in patients with chronic rhinosinusitis based on a metagenomic analysis

Abstract: These results suggest that patients with CRS have altered nasal microbiota and decreased diversity in bacterial compositions as well as increased S. aureus abundance in those patients with polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 32 publications
9
137
0
3
Order By: Relevance
“…In this study, CRS patients exhibited more bacterial abundance but less diversity in nasal lavage specimens. 447 In a large cohort of patients, Ramakrishnan et al 445 examined microbiome alterations by phenotype and noted that CRS patients with asthma or purulence had markedly different microbiota. In this study, the…”
Section: S55mentioning
confidence: 99%
“…In this study, CRS patients exhibited more bacterial abundance but less diversity in nasal lavage specimens. 447 In a large cohort of patients, Ramakrishnan et al 445 examined microbiome alterations by phenotype and noted that CRS patients with asthma or purulence had markedly different microbiota. In this study, the…”
Section: S55mentioning
confidence: 99%
“…Boase et al 9 and Choi et al 11 found an increased bacterial load in CRS patients and suggested that a rise in bacteria, possibly from external sources, causes CRS. However, Abreu et al, 10 , Feazel et al 12 and Ramakrishnan et al 13 found no difference in burden between the two groups.…”
Section: Bacterial Loadmentioning
confidence: 99%
“…Traditional culture-dependent methods fail to truly represent the sinus microbiome 9,15 , so truly accurate insights into CRS versus healthy microbiomes are from a currently limited number of molecular-based studies [9][10][11][12][15][16][17][18] .…”
Section: Crs and The Sinus Microbiomementioning
confidence: 99%
See 2 more Smart Citations